Case series of Fournier's gangrene: Affected body surface area – The underestimated prognostic factor. (April 2017) - Morais, Henrique; Neves, Jessica; Maciel Ribeiro, Hugo; Ferreira, Marta; Guimarães, Narcisa; Azenha, Nuno; Dias, Raquel; Fonseca, Alice; Conceição, Lucilia
Abstract: Objectives: Identifying the factors affecting the outcome of patients with Fournier's Gangrene and assaying the accuracy of the Fournier Gangrene Severity Index (FGIS), the Uludag score (UdS), affected Body Surface Area (BSA) and the Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) model as prognostic tools. Materials and methods: Retrospective study involving all patients with Fournier's gangrene treated in our Hospital between January 2008 and December 2015. The epidemiological, clinical, biochemical and management data of these patients was obtained and analyzed. Results: The series includes 19 patients, 14 male and 5 female, with a median age of 70 (62; 78, 5) years. The mortality rate was 21%. From the data analyzed, only the affected BSA (BSA>3.25%) was associated with mortality (p = 0.016). None of the established scores (FGSI; UdS; LRINEC) proved to be a useful tool for predicting mortality. The combination of affected BSA and FSGI (FGSI≥9 or BSA>3.25%), (p = 0.004 ) and the combination of the affected BSA and the LRINEC model (LRICEC≥8 and BSA>3.25%), (p = 0.004) led to a major improvement in these scores. Conclusions: Affected BSA is a useful prognostic factor in Fournier's gangrene. The existing prognostic scores can be improved with the introduction of this factor. Highlights: Fournier's gangrene is a devastating disease that challenges the modern medicine. Predicting the outcome may be a crucial step in his management. Current scores are not always effective. Affected body surface area is a key factor in patients outcome. Current scores may be improved with the inclusion of affected body surface area.